Developing Pedagogically Aligned AR Media for Teaching Polyhedra in Junior Secondary Education - Arif Abdul Haqq; Hendri Handoko; Reo Al Farizi (ITEJ (Information Technology Engineering Journals), 2025)
This study presents the design and evaluation of marker-based augmented reality instructional media using Unity and Vuforia to support polyhedra learning in junior high school geometry. The development followed the 4D model and was grounded in a five-phase learning trajectory consisting of exploration, manipulation, analysis, application, and reflection. The AR media features interactive 3D polyhedron models, net unfolding animation, and formula overlays, each activated through printed markers. The design was informed by students’ learning needs, particularly difficulties in visualizing shapes, distinguishing surface area from volume, and applying geometric formulas correctly. Expert validation using Aiken’s V confirmed strong instructional alignment. Student perception data, classroom observations, and teacher interviews indicated that the media enhanced spatial reasoning, improved engagement, and encouraged verbal mathematical discourse. The findings support the integration of AR into structured pedagogical sequences and demonstrate its potential to improve geometry instruction in diverse classroom settings.